2015
DOI: 10.1002/joc.4348
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed trends over the southwestern Atlantic Ocean, between 33° and 50°S

Abstract: Surface scalar wind speed trends (from 1979 to 2009) at the southwestern Atlantic Ocean, between 33° and 50°S and 55° and 70°W, were estimated from the NCEP/NCAR I (NR1) and the Climate Forecast System Reanalysis (CFSR) using Sen's slope. Trends were tested using the seasonal Mann–Kendall test. Scalar wind speed trends computed from NR1 database were positive throughout the whole study area, with values ranging from +0.01 to +0.03 m s−1 year−1. On the contrary, wind speed trends computed from CFSR database wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Positive values correspond to increasing trends whereas negative values denote slowing wind speeds. This linear regression method has been used instead of a more complex technique such as the Theil-Sen Slope estimator (Theil 1950, Sen 1968) since it has been demonstrated that they produce very similar results (Pescio et al 2016).…”
Section: Data Description and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Positive values correspond to increasing trends whereas negative values denote slowing wind speeds. This linear regression method has been used instead of a more complex technique such as the Theil-Sen Slope estimator (Theil 1950, Sen 1968) since it has been demonstrated that they produce very similar results (Pescio et al 2016).…”
Section: Data Description and Methodologymentioning
confidence: 99%
“…The observations used in the reanalyses are not the only source of uncertainty affecting these products, also there are some errors in the assimilation systems that can have an impact on the quality of the reanalyses (Reichler and Kim 2008). To address the uncertainty inherent in the estimation of longterm trends (Liléo et al 2013, Nchaba et al 2017, Pescio et al 2016 the use of more than one reanalysis has been recommended. A multi-reanalysis approach allows the quantification of the individual reanalysis uncertainty and the identification of robust signals that could be distinguished from artifacts in the observational data sources.…”
Section: Introductionmentioning
confidence: 99%
“…Different changes in atmospheric processes have been previously reported for the southwestern Atlantic Ocean (Gregg & Conkright, 2002;Severov et al, 2004;Simionato et al, 2005;Dragani et al, 2013;Pescio et al, 2015), and in particular for the Argentine platform (Martos & Piccolo, 1988;Lucas et al, 2005;Auad & Martos, 2012;Delgado et al, 2012). The passage of cyclones produced from baroclinic and lee topographic instability of the westerlies seemed to cause the high temporal variability of the winds over the southeastern South Atlantic (Gan & Rao, 1991).…”
Section: Discussion 41 Shifts In Wind and Temperature Patterns Alongmentioning
confidence: 73%
“…The raw analysis of the NR1 data shows no temporal trend in variables, except in the wind (Pescio et al, 2015) where we find an increment of 1.7 ± 0.9 cm s −1 /yr at a 95% confidence level. The analogous result for the B node is 2.2 ± 0.9 cm s −1 /yr.…”
Section: Datamentioning
confidence: 89%